POLIGAMI DALAM PERSPEKTIF ASGHAR ALI ENGINEER DAN RELEVANSINYA DENGAN KONTEKS INDONESIA (Mazahib, 2007)
Polygamy has become a polemic among Islamic jurists (fuqaha’) since the classical era of Islamic jurisprudence. The core polemic lies on the issue whether polygamy is permitted, prohibited or permitted with some requirements. This article is to analyze Ashgar Ali Engineer’s opinion on the legal status of polygamy. According to Ashgar, the al-Nisa chapter : 3 concerning about  polygamous permissibility must be construed in the light of the al-Nisa chapter : 1 which concerns of doing justice to orphans. This understanding then suggest, Asghar further argue, the permissibility of polygamy is contextual in Islam. Thus, it is possible that its implementation in Muslim country is strictly limited as long as the context where Muslims live required so.